Sodium glucose co-transporter 2 (SGLT2) inhibition via dapagliflozin improves diabetic kidney disease (DKD) over time associatied with increasing effect on the gut microbiota in db/db mice - Wu, Jiajia; Chen, Yan; Yang, Huinan; Gu, Leyi; Ni, Zhaohui; Mou, Shan; Shen, Jianxiao; Che, Xiajing (Frontiers in Endocrinology, 2023)
Background: The intestinal microbiota disorder gradually aggravates during the progression of diabetes. Dapagliflozin (DAPA) can improve diabetes and diabetic kidney disease（DKD）. However, whether the gut microbiota plays a role in the protection of DAPA for DKD remains unclear. Methods: To investigate the effects of DAPA on DKD and gut microbiota composition during disease progression. In our study, we performed 16S rRNA gene sequencing on fecal samples from db/m mice (control group), db/db mice (DKD model group), and those treated with DAPA (treat group) at three timepoints of 14weeks\18weeks\22weeks. Results: We found that DAPA remarkably prevented weight loss and lowered fasting blood glucose in db/db mice during disease progression, eventually delaying the progression of DKD. Intriguingly, the study strongly suggested that there is gradually aggravated dysbacteriosis and increased bile acid during the development of DKD. More importantly, comparisons of relative abundance at the phylum level and partial least squares-discriminant analysis (PLS-DA) plots roughly reflected that the effect of DAPA on modulating the flora of db/db mice increased with time. Specifically, the relative abundance of the dominant Firmicutes and Bacteroidetes were not meaningfully changed among groups at 14 weeks as previous study described. Interestingly, they were gradually altered in the treat group compared to the model group with longer intervention of 18 weeks and 22 weeks. Furthermore, the decrease of Lactobacillus and the increase of norank_f__Muribaculaceae could account for the differences at the phylum level observed between the treat group and the model group at 18 weeks and 22 weeks. Conclusion: We firstly found that the protective effect of DAPA on DKD may be related to the dynamical improvement of the gut microbiota over time, which was possibly associated with the effect of DAPA on bile acid pool and its antioxidation effect.